A Novel Longitudinal Training Experience in Obesity Medicine for Internal Medicine Residents - Neuman, Melissa; Kane, Jamie; Kline, Myriam; Shafer, Rebecca; Lambert, Douglas C (Journal of graduate medical education, 2024)
Treatment of obesity is a public health priority. However, little training in obesity medicine is currently integrated into residency programs. We integrated a 12-month obesity medicine training experience within a New York internal medicine residency program. We describe the structure, feasibility and acceptability, resident assessments, and patient weight loss outcomes of an optional longitudinal obesity medicine training experience for internal medicine residents. Between July 2016 and June 2021, 26 second-year residents participated in the 12-month program, which comprised 10 educational/clinical sessions overseen by obesity medicine attendings. Residents completed baseline and post-program 5-point surveys of knowledge, competence, and attitudes. Differences at 12 months were analyzed using paired tests. Resident patient weight loss was analyzed using the Wilcoxon signed rank test. The training experience was successfully integrated over the study period and remains ongoing at present, demonstrating feasibility and acceptability. Fourteen of 26 (54%) residents completed post-program surveys. Significant improvements in all measures of knowledge and competence were seen. The greatest improvements were in comfort discussing weight loss with patients (+1.1; 95% CI 0.8-1.5; <.001) and prescribing weight loss medications (+1.4; 95% CI 1.1-1.6; <.001). The 98 patients seen by residents lost an average of 4.5 kilograms (95% CI 3.0-6.0; <.001). The training experience was feasible and acceptable, and demonstrated improvements in resident outcomes and patient weight.